On the 91/17 pattern in the brackish ichnofabric - Arifullah, Ery (Berita Sedimentologi, 2021)
From previous research, I have identified what ichnotaxa dominate each ichnofabric unit and how many ichnotaxa are taking up a share of the total observed ichnofabric units. The contribution of this paper is the 91/17 pattern. The point of this pattern is that only 17% ichnotaxa (6 of 34 ichnotaxa) had 91% of the total ichnofabric units that were observed. In addition, the six ichnotaxa tend to be more monospecific. These are the most effective strategies for the animal to survive by constructing the most essential structures. These strategies are common in brackish paleoecology in the fluvial-marine transition zone.